ANALISIS KEPATUHAN MASYARAKAT KABUPATEN JOMBANG TERHADAP KEBIJAKAN PENGGUNAAN MASKER PADA MASA PANDEMI COVID-19 - Winanda, Nieke Rudyanty; Hidayat, Muhammad Nur; Hudallah, Hudallah (JPAP: Jurnal Penelitian Administrasi Publik, 2021)
The global covid-19 pandemic has affected all sectors of human life. Humans have to adapt the new ways of life. One of the new ways of life is to use a mask when doing activities outside the home. Health protocol policies, including the use of masks, are a form of government responsibility in overcoming the covid-19 pandemic. The policy will not be able to achieve success if it is not supported by the public. Health protocol policies, including the use of masks, have the main goal of breaking the chain of the spread of covid-19. In Jombang regency regulation of health, protocols are regulated in Peraturan Bupati no. 57 Tahun 2020. This study was conducted to find out how the public adheres to these policies and regulations. This study uses qualitative methods using primary and secondary data. Data collections techniques used are interviews, observation and, documentation. The data analysis used in this study is the Miles and Huberman model which consists of data reduction, data display and, conclusion drawing or verification. The results of this study indicate that the public is obedient to the policies and rules for the use of masks, only to obey the regulation and avoid sanctions and not to realize the main goal of the policy, which is to break the chain of the spread of covid-19 so that the pandemic can end soon.